ETUDE GEOCHIMIQUE DE LA MINERALISATION POLYMETALLIQUE DE LA ZONE D’AMSAGA (DORSALE DE RGUEÏBAT, MAURITANIE) - Ahmed Hamoud; Said Chakiri; Hassan El Hadi; Bouamar Baghdad; Khadija Zahidi (European Scientific Journal, ESJ, 2014)
The Amsaga Zone is of a major importance, due to its position in the extreme south west of the Archean part of the Rgueibat shield, particulary to its location close to the Akjoujt Copper mine. Some dating migmatites indicate that granulite metamorphism affecting most Amsaga units took place between 3 and 2.7 Ga. The results of soil geochemistry and field mapping have showed significant potential for polymetallic mineralization, and have enabled to understand the relationships between rock units and structures of mineralization controls such as faults and shear zones. This context reflects a tectonic control of implementation of the mineralization by movements in faults and ductile shear zones.